2001
DOI: 10.1007/s005310000142
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy of Upper Cretaceous-Palaeogene sequences in the southern and eastern Menderes Massif (western Turkey)

Abstract: The stratigraphy of the uppermost levels of the Menderes Massif is controversial and within its details lie vital constraints to the tectonic evolution of south-western Turkey. Our primary study was carried out in four reference areas along the southern and eastern Menderes Massif. These areas lie in the upper part of the Menderes metamorphic cover and have a clear stratigraphic relationship and contain datable fossils. The first one, in the Akbük±Milas area, is located south-east of Bafa Lake where the Milas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 12 publications
0
47
0
2
Order By: Relevance
“…The overlying metasedimentary cover sequence consists, from bottom to top, of garnet micaschist, mica schist and quartzite with intercalations of Permo-Carboniferous black marble, a thick succession of Mesozoic emery-and rudist-bearing marble, and Palaeocene flysch-like sediments (Dürr 1975;Þaglayan et al 1980;Ş engör et al 1984;Okay 1985Okay , 1989Konak et al 1987;Dora et al 1995;Özer 1998Özer et al 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The overlying metasedimentary cover sequence consists, from bottom to top, of garnet micaschist, mica schist and quartzite with intercalations of Permo-Carboniferous black marble, a thick succession of Mesozoic emery-and rudist-bearing marble, and Palaeocene flysch-like sediments (Dürr 1975;Þaglayan et al 1980;Ş engör et al 1984;Okay 1985Okay , 1989Konak et al 1987;Dora et al 1995;Özer 1998Özer et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…These hippuritid species are well known and have been identified in Santonian-Campanian marbles of the southern sector of the Menderes Massif, around the Akbük-Milas and Yatagan-Kavaklıdere areas (Özer 1993, 1998; Özer et al 2001). Þaglayan et al 1980;Dora et al 1990Dora et al , 1995Gessner 2000;Özer et al 2001;Okay 2001). Inset shows location of Fig.…”
Section: Stratigraphy and Palaeontologymentioning
confidence: 90%
“…A Late Paleozoic to Late Cretaceous sedimentary cover, deposited on top of late Proterozoic (Cadomian) basement, shows a progressive deepening of depositional environments ending with a Late Paleocene-Early Eocene olistostrome (Ö nay 1949;Dürr 1975;Caglayan et al 1980;Ö zkürt and Koçyigit 1983;Sengör et al 1984;Konak et al 1987;Ö zer 1998;Ö zer et al 2001). In the Dilek peninsula, rock assemblages closely resembling the Cycladic Blueschists that have given Eocene ages (40 Ma) are thrust over the Menderes massif Candan and Dora 1998;Oberhänsli et al 1997Oberhänsli et al , 1998Okay et al 2001b;Cetinkaplan 2002;Ring et al 2007).…”
Section: The Menderes Massif and Lycian Nappesmentioning
confidence: 96%
“…The Selimiye formation passes up into a very characteristic marble-phyllite-quartzite series, the Göktepe formation, which have yielded Permian and Carboniferous coral, algae, brachiopods and fusulinid-type foraminifera in several localities (e.g., Phillippson 1918;Önay 1949;Dürr 1975). The Göktepe formation is overlain by emery-and metabauxite-bearing marbles, which contain Triassic and Cretaceous macro and microfossils (Dürr 1975;Özer et al 2001). The neritic carbonate series extend up to Campanian, and are overlain by red pelagic marbles with Late Campanian-Late Maastrichtian Globotruncana species (Özer et al 2001).…”
Section: Lithostratigraphic Correlationmentioning
confidence: 97%
“…Stratigraphic, metamorphic and isotopic data from the Çine and Ödemiş submassifs (stratigraphy : Dürr 1975;Çaǧlayan et al 1980;Okay 2001;Özer et al 2001;metamorphism: İzdar 1971;Evirgen and Ataman 1982;Evirgen 1984, 1985;Evirgen and Ashworth 1984;Okay 2001; isotopic data: Satır and Friedrichsen 1986;Hetzel and Reischmann 1996;Hetzel et al 1998;Loos and Reischmann 1999;Koralay et al 2001). The "nappe" terminology of Ring et al (1999) and Gessner et al (2001aGessner et al ( , 2001b is shown for comparison.…”
Section: Figmentioning
confidence: 98%